1998
DOI: 10.1063/1.872949
|View full text |Cite
|
Sign up to set email alerts
|

Effect of edge neutrals on the low-to-high confinement transition threshold in the DIII-D tokamak

Abstract: To study the effect of edge neutrals on the low-to-high confinement transition threshold, a broad range of plasma discharges has been analyzed. These discharges vary by gas puffing and pumping rates, position of the X point, and line-averaged density. It is shown that the determination of the neutral density (or neutral pressure) in the scrape-off layer (SOL) can give a misleading indication of the neutral population inside the separatrix. An increase of neutral density in the SOL creates an increase of plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
53
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 37 publications
8
53
0
Order By: Relevance
“…This non-linearity has also been recognized recently by modeling done for DIII-D discharges. 4 Thus, in assessing the influence of neutrals, the wall neutral pressure measurement can lead to wrong conclusions. Shown in Fig.…”
Section: A Particle Balancementioning
confidence: 99%
“…This non-linearity has also been recognized recently by modeling done for DIII-D discharges. 4 Thus, in assessing the influence of neutrals, the wall neutral pressure measurement can lead to wrong conclusions. Shown in Fig.…”
Section: A Particle Balancementioning
confidence: 99%
“…Neutral particles have a strong influence on the particle, momentum and energy balance in the edge plasma through processes such as charge exchange and ionization, so there are many possible physical effects. Recent studies indicate that it is the neutral population inside the separatrix, rather than the SOL neutrals, that correlates with the H-mode transition, 3,5 and that the required threshold power scales with the ion-neutral frictional damping rate. 3 As this friction is typically dominated by ion-neutral charge exchange, in this paper we will use the terms "friction"…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of experiments have been devoted to studying the effect of neutral particle influxes on the high-confinement mode (H-mode), [1][2][3][4][5] and it has been shown that the neutrals can significantly affect the transition from the low to high confinement modes (the L-H transition). The physical mechanism by which neutrals influence this transition has not yet been identified, and it is not known whether the same mechanism is operative in all experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Since the UEDGE and OEDGE codes are the primary tools used on the DIII-D device, this report will focus on the development of these codes. Other codes have been used for analysis of DIII-D boundary plasmas [4][5][6][7][8][9][10][11][12]. Space limitations, however, prevent detailed discussion of all code results, so we have chosen to focus on the results of the codes which are most frequently 4 used.…”
Section: Introductionmentioning
confidence: 99%